Bengal raag - Soomro, Durdana; Hameed, Ghazala (Dhaka : Writers.ink : Distributed by University Press, 2006)
Autobiographical fiction of the daughters of a Pakistani civil servant about their childhood in Bangladesh.
Includes bibliographical references (p. [149]).
ENH
Keywords: Pakistani fiction (English)